Understanding Concepts of Acquisition of English As a Second Language: An analysis of theories in language acquisition (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Education in English language arts borrows its theoriesfrom a range of disciplines and numerous theorists. These theories can bemainly classified into three groups on the basis of three prominent views - thebehaviourist view, the innatist view and the interactionist view This sectionanalyses these three views. The behaviourist view of language acquisition issimplistic and general. According to this view, language learning, like otherkinds of learning, occurs as a result of the environment shaping an individualwith a given 1Q. They hold that an individual is reinforced positively ornegatively for responses to various stimuli. One can make sure that behaviourwill recur by administering positive reinforcement, when a desired behaviouroccurs and by administering negative reinforcement when an undesired behaviouroccurs. This view of language learning maintains that when a child grows older,reinforcement becomes progressively more contingent on how nearly the child'slanguage matches the adults.